2019
DOI: 10.1007/s12325-019-01128-9
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea in COPD: New Mechanistic Insights and Management Implications

Abstract: Dyspnea is the most common symptom experienced by patients with chronic obstructive pulmonary disease (COPD). To avoid exertional dyspnea, many patients adopt a sedentary lifestyle which predictably leads to extensive skeletal muscle deconditioning, social isolation, and its negative psychological sequalae. This ''dyspnea spiral'' is well documented and it is no surprise that alleviation of this distressing symptom has become a key objective highlighted across COPD guidelines. In reality, this important goal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
1
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(135 citation statements)
references
References 112 publications
2
122
1
10
Order By: Relevance
“…End-inspiratory lung volume during exercise is typically midway between FRC and TLC or even higher ( Younes and Burks, 1985 ; Neder et al, 2003 ). Inspirations during exercise hyperpnea in highly trained athletes and patients with expiratory flow limitation such as in patients with chronic obstructive pulmonary disease are initiated at or above FRC and end-inspiratory lung volume will approach TLC ( Johnson et al, 1992 ; Dempsey et al, 2008 ; McKenzie, 2012 ; O’Donnell et al, 2019 ). In addition, shortening velocity of the respiratory muscles has to increase during exercise hyperpnea ( Prioux et al, 2000 ; Neder et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…End-inspiratory lung volume during exercise is typically midway between FRC and TLC or even higher ( Younes and Burks, 1985 ; Neder et al, 2003 ). Inspirations during exercise hyperpnea in highly trained athletes and patients with expiratory flow limitation such as in patients with chronic obstructive pulmonary disease are initiated at or above FRC and end-inspiratory lung volume will approach TLC ( Johnson et al, 1992 ; Dempsey et al, 2008 ; McKenzie, 2012 ; O’Donnell et al, 2019 ). In addition, shortening velocity of the respiratory muscles has to increase during exercise hyperpnea ( Prioux et al, 2000 ; Neder et al, 2003 ).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the V E :dyspnea relationship, which is limited when respiratory mechanics are impaired, EMGdi %max robustly correlates with dyspnea in health and across disease severity ( 50 , 74 ). Dyspnea is thought to reflect awareness of the mismatch that results when increased IND does not or cannot result in an adequate mechanical or ventilatory response ( 75 ). While not present during resting tidal breathing in health, the stressor of exercise or pathophysiologic processes of disease typically provoke sensations of dyspnea ( 76 ).…”
Section: Neural Drive In the Evaluation Of The Breathless Patientmentioning
confidence: 99%
“…This, in turn, further increases IND and ventilation. When paired with a rapid, shallow breathing pattern increasing dead space, and underlying expiratory flow limitation leading to dynamic hyperinflation and encroachment of tidal volume on critical inspiratory reserve ( Figure 2E ) ( 119 , 120 ), early cessation of exercise and a higher symptom burden for a given work rate ensue ( 75 ). In ILD, low diffusing capacity and low pulmonary compliance result in increased ventilatory drive and a rapid, shallow breathing pattern due to limited V T expansion, ultimately also leading to premature termination of exercise and exaggerated dyspnea ( 55 ).…”
Section: Neural Drive In the Evaluation Of The Breathless Patientmentioning
confidence: 99%
“…Assuming stability of TLC, the resting IC and inspiratory reserve (IRV) showed the operating position of V T relative to TLC. The smaller the resting IC, the shorter the exercise time before V T reached plateau and dyspnea abruptly escalates [38]. A four-year longitudinal study reported that significant reductions in peak VȮ 2 and V̇E were related to a decrease in resting IC [39].…”
Section: Discussionmentioning
confidence: 99%